A Study on the solar radiation incident upon the overhead water tanks in Saudi Arabia with different configurations - Khurshid, Hassan; Silaipillayarputhur, Karthik (International Journal of Engineering and Technology, 2018)
Saudi Arabia is one of the warmer countries in the Middle East region. In the summer months, the ambient temperature reaches 50°C on regular basis. This high temperature has a direct effect on the elevation of water temperatures inside the domestic and commercial over-head tanks. The tanks are predominantly installed on the roof of the buildings without any shade or insulation and are exposed to the direct irradiation from the sun. The tank material is not capable of reducing the effect of solar radiation. Therefore, water gets very hot in the afternoon that it is impossible for the occupants of the residential buildings to take a shower or even wash their hands. This paper studied the effect of solar irradiation on the water temperature in the over-head storage water tanks during the summer months. The temperature rise in the water storage tank was considered for different cases, (i.e.) a free standing tank exposed to direct sun’s irradiation, a tank with shade, a tank with fiber glass insulation, and a tank having insulation along with shade. An analytical model was developed to study the effects of sun’s irradiation and the results were compared with that of experimentation. The results from the water storage tank having insulation exhibited encouraging results.